Comparative Analysis of Power Quality of Solar PV Power Only, Hybrid Solar PV–Grid Power, and National Grid Power Only for SMEs: The Case of a Laundry Shop in Ghana - Godwill Nkrumah Yeboah; Richard Opoku; Felix Uba; Gidphil Mensah; Charles Kofi Kafui Sekere (Journal of Engineering)
Globally, small and medium-sized enterprises (SMEs) mainly depend on the national grid to provide energy for their daily activities. The quality of energy supplied affects the operation of their appliances and work. In this study, an analysis has been conducted on the power quality of three different sources of energy: solar PV power only, hybrid solar PV–grid power, and national grid power only, and how they affect the operation of appliances in a laundry shop in Ghana. Data were obtained using data logs from a 5-kVA hybrid inverter setup with a 3-kW solar panel for 4 months. Electrical power quality parameters monitored were voltage level, frequency, power factor, sag/undervoltage, swell/overvoltage, voltage interruption, and flicker. The study revealed that operating a business on solar PV only assured the end user of the best electrical power quality. The hybrid solar PV–grid system is also a good candidate for bad weather where the solar PV would not be able to yield the expected energy. The national grid proved to be of lower quality and a potential hazard to appliances.